Non-breeding Shelduck Tadorna tadorna in the southwest Netherlands: effects of habitat changes on distribution, numbers, moulting sites and food - Meininger, Peter L; Snoek, Harold (Wildfowl, 1992)
In the Delta area of southwest Netherlands, several sea-arms were recently (partially) changed into fresh or saltwater lakes. In the Oosterschelde a storm-surge barrier was built. All these activities resulted in a total reduction of intertidal area from 31,950 ha in 1960 to 19,615 ha in 1990. Shelduck are present in the Delta area throughout the year, with 8000-10,000 in January. After estuarine areas were changed into freshwater lakes, the peak in Shelduck numbers showed a shift from winter to spring and summer. This is probably related to a change in food resources exploited by Shelduck from predominantly marine invertebrates in the tidal situation to predominantly Chironomid larvae and their pupae in the freshwater situation. The latter food source shows peak populations in late spring. In the most important wintering area, the Oosterschelde, the percentual decreases in winter numbers in the periods 1979-83 and 1988-90, in both the entire estuary (including areas turned into freshwater lakes; -52%) and in the areas that remained tidal 40%), were considerably higher than 22% of tidal Shelduck habitat lost. In addition to habitat loss, the most likely explanation for this decrease is the considerable recent decline in Hydrobia populations in this area. Hydrobia was shown to be the most important food item in saline tidal areas. The relatively high mortality among Shelduck in the Oosterschelde during the winters of 1985-87 may have been another cause of the decrease in the local winter population in 1988-90. Based on ringing recovery data, it is presumed that birds moulting in the Delta area mainly originate from northwest France, Belgium and the Delta area. A part of the Delta population moves to the German Wadden Sea instead of moulting locally. Shelduck present in winter concern local breeding birds, birds from northerly breeding areas, and birds breeding in France, Belgium and England. Concentrations of moulting Shelduck in the Delta area are found in two areas, Westerschelde (several thousands annually) and Haringvliet (up to 2000 on freshwater), and not in the most important wintering area, the Oosterschelde. The presence of safe and undisturbed areas during moult could well be more important than the availability of food.